2020
DOI: 10.1016/j.eururo.2019.07.031
|View full text |Cite
|
Sign up to set email alerts
|

Mortality and Hospitalization Risk Following Oral Androgen Signaling Inhibitors Among Men with Advanced Prostate Cancer by Pre-existing Cardiovascular Comorbidities

Abstract: Background: Elderly patients (≥65 yr) with advanced prostate cancer and cardiovascular disease (CVD) conditions are often excluded from clinical trials of abiraterone acetate (AA) or enzalutamide (ENZ). Consequently, little is known about the effects of these medications on these vulnerable patients.Objective: To assess the short-term outcomes of AA and ENZ in patients with pre-existing CVDs. Design, setting, and participants:A population-based retrospective study. The Surveillance, Epidemiology, and End Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 25 publications
(33 reference statements)
3
35
0
5
Order By: Relevance
“…These effects may contribute to the recognized association between enzalutamide treatment and higher short-term Annals of Oncology mortality in men with pre-existing cardiovascular disease. 25 Asthenia and other hard-to-define central nervous system (CNS) effects, including mental status changes and mental impairment, are also noted to occur with potent AR antagonists. 26 One hypothesis is that some of these effects may be attributable to a GABAergic action in the CNS.…”
Section: Discussionmentioning
confidence: 99%
“…These effects may contribute to the recognized association between enzalutamide treatment and higher short-term Annals of Oncology mortality in men with pre-existing cardiovascular disease. 25 Asthenia and other hard-to-define central nervous system (CNS) effects, including mental status changes and mental impairment, are also noted to occur with potent AR antagonists. 26 One hypothesis is that some of these effects may be attributable to a GABAergic action in the CNS.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, there has been a growing concern about their safety in real-world populations, especially in the elderly or those with CV diseases. A population-based retrospective study from The Surveillance, Epidemiology, and End Results (SEER) database of patients using abiraterone or enzalutamide (n = 3,876) revealed that men with coexisting CV comorbidities have a higher mortality threat compared to individuals without a history of CV disorders ( Lu-Yao et al, 2020 ). However, there is also evidence that appropriate control of CV comorbidities before the treatment initiation may substantially reduce the CV risk of the prescribed therapy ( Verzoni et al, 2016 ).…”
Section: Cardiovascular Complications Of Prostate Cancer Treatmentmentioning
confidence: 99%
“…The AR signaling has been a target of immense attention because of its involvement in PC. Indeed, the AR signaling pathway's molecular level defects can trigger PC growth, differentiation, metastasis, invasion, and aggressiveness [107]. New insights given to miRNAs and their interactions with different signaling cascades have become more and more significant, as they are chief modulators of almost all cells' machinery [108].…”
Section: Discussionmentioning
confidence: 99%